Covalent Organic Frameworks as Negative Electrodes for High‐Performance Asymmetric Supercapacitors - Kandambeth, Sharath; Jia, Jiangtao; Wu, Hao; Kale, Vinayak S.; Parvatkar, Prakash T.; Czaban‐Jóźwiak, Justyna; Zhou, Sheng; Xu, Xiangming; Ameur, Zied Ouled; Abou‐Hamad, Edy; Emwas, Abdul‐Hamid; Shekhah, Osama; et al. (Advanced energy materials, 2020)
New covalent organic frameworks (COFs), encompassing redox‐functionalized moieties and an aza‐fused π‐conjugated system, are designed, synthesized, and deployed as negative electrodes in asymmetric supercapacitors (ASC), for the first time. The Hex‐Aza‐COFs are synthesized based on the solvothermal condensation reaction of cyclohexanehexone and redox‐functionalized aromatic tetramines with benzoquinone (Hex‐Aza‐COF‐2) or phenazine (Hex‐Aza‐COF‐3). The redox‐functionalized Hex‐Aza‐COFs show a specific capacitance of 585 F g−1 for Hex‐Aza‐COF‐2 and 663 F g−1 for Hex‐Aza‐COF‐3 in a three‐electrode configuration. These values are the highest among reported COF materials and are comparable with state‐of‐the‐art pseudocapacitive electrodes. The Hex‐Aza‐COFs exhibit a wide voltage window (0 to −1.0 V), which allow the construction of a two‐electrode ASC device by combining them with RuO2. The complementary potential windows of Hex‐Aza‐COF‐3 and RuO2 enable an asymmetric device with a high voltage window of 1.7 V. The RuO2//Hex‐Aza‐COF‐3 ASC device achieves an energy density value of 23.3 W h kg−1 at a power density of 661.2 W kg−1. The newly developed negative COF materials open new prospects for the development of high‐performance ASCs. New redox‐functionalized Hex‐Aza covalent organic frameworks (Hex‐Aza‐COFs) are synthesized and applied as negative electrodes in asymmetric supercapacitors. These Hex‐Aza‐COFs show a specific capacitance of 585 F g−1 for Hex‐Aza‐COF‐2 and 663 F g−1 for Hex‐Aza‐COF‐3 in a three‐electrode configuration at 1 A g−1. The asymmetric device composed of Hex‐Aza‐COF and ruthenium oxide, displays a broad voltage window of 1.7 V.